Implementar el Sistema de Gestión de la Seguridad y Salud en el Trabajo basado en el Capítulo 6 del Decreto 1072 de 2015, La Resolución 1111 de 2017 y el Decreto 052 de 2017 en la Agencia de Aduanas Internacional S.A.S Nivel 2 (2019)
The improvement plan was carried out in order to comply with the objectives through some proposed activities, as well as the definition of roles and responsibilities in SG-SST which are found in the job profile manuals, followed by an awareness plan which is aimed at the entire company, and a training plan according to a schedule of training in SG-SST, management indicators, emergency plan and an internal audit of the system to assess the level of compliance in which the company is at the end of this grade work.